EXISTENCE OF THE POSSIBILITY OF STRESS AMONG TEACHERS OF PHYSICAL EDUCATION SCHOOLS ELEMENTARY AND MIDDLE LEVEL NETWORK STATE CENTRAL DISTRICT OF THE CITY OF GOOD VIEW - RR (Fiep Bulletin - online, 2014)
Valuing the teacher in their educational activity, set up a new vista for discursion stress in the life of the teacher, encouraging new research, inform the academic population, with the ultimate goal of this compound, contribute to the knowledge of an installment teachers who teaches Physical Education and as a result know aspects of your health, the reaction of this stress-related professional and meet the teacher within the school . The theme called: “the possibility of existence of stress among physical education teachers who teach in schools of primary and secondary levels located in Centro neighborhood of Boa Vista - RR " , covers the universal idea and genre defining characteristic of monographic . The problem situation is to analyze whether there are possibilities of teachers included in range of research present and indicative symptoms to stress. For the configuration of the monograph began the first literature search , selecting documents that fit the needs and character of the research , soon after , as a second step , we elaborated a questionnaire was applied in the research field . In designing the questionnaire, previously held an informal interview with some teachers' academics students Full Degree in Physical Education in order to discover the possible stressors within the school. Analyzing the results obtained in the field survey, it was observed that all the teachers surveyed are unaware of what is stress. They say they do not feel physical fatigue or mental. Just as everyone maintains a grating friendly with other school staff, and 100 % of the teachers surveyed are satisfied with their work. According to the results of research there is a possibility of the occurrence of 23.3% stress between teachers interviewed a relatively high percentage with respect to the sample.
Keywords: Stress; Physical Education; Work; Health